Heparan sulfate co-immobilized with cRGD ligands and BMP2 on biomimetic platforms promotes BMP2-mediated osteogenic differentiation. (15th September 2020) - Sefkow-Werner, Julius; Machillot, Paul; Sales, Adria; Castro-Ramirez, Elaine; Degardin, Melissa; Boturyn, Didier; Cavalcanti-Adam, Elisabetta Ada; Albiges-Rizo, Corinne; Picart, Catherine; Migliorini, Elisa
ABSTRACT: The chemical and physical properties of the extracellular matrix (ECM) are known to be fundamental for regulating growth factor bioactivity. The role of heparan sulfate (HS), a glycosaminoglycan, and of cell adhesion proteins (containing the cyclic RGD (cRGD) ligands) on bone morphogenetic protein 2 (BMP2)-mediated osteogenic differentiation has not been fully explored. In particular, it is not known whether and how their effects can be potentiated when they are presented in controlled close proximity, as in the ECM. Here, we developed streptavidin platforms to mimic selective aspects of the in vivo presentation of cRGD, HS and BMP2, with a nanoscale-control of their surface density and orientation to study cell adhesion and osteogenic differentiation. We showed that whereas a controlled increase in cRGD surface concentration upregulated BMP2 signaling due to β3 integrin recruitment, silencing either β1 or β3 integrins negatively affected BMP2-mediated phosphorylation of SMAD1/5/9 and alkaline phosphatase expression. Furthermore, the presence of adsorbed BMP2 promoted cellular adhesion at very low cRGD concentrations. Finally, we proved that HS co-immobilized with cRGD both sustained BMP2 signaling and enhanced osteogenic differentiation compared to BMP2 directly immobilized on streptavidin, even with a low cRGD surface concentration. Altogether, our results show that HS facilitated and sustained the synergy between BMP2 and integrin pathways and that the co-immobilization of HS and cRGD peptides optimised BMP2-mediated osteogenic differentiation. Statement of significance The growth factor BMP2 is used to treat large bone defects. Previous studies have shown that the presentation of BMP2 via extracellular matrix molecules, such as heparan sulfate (HS), can upregulate BMP2 signaling. The potential advantages of dose reduction and local specificity have stimulated interest in further investigations into biomimetic approaches. We designed a streptavidin model surface eligible for immobilizing tunable amounts of molecules from the extracellular space, such as HS, adhesion motifs (cyclic RGD) and BMP2. By studying cellular adhesion, BMP2 bioactivity and its osteogenic potential we reveal the combined effect of integrins, HS and BMP2, which contribute in answering fundamental questions regarding cell-matrix interaction. Graphical abstract: Image, graphical abstract